Maximum Occupancy: A creative and critical exploration of how Text World Theory can be used when writing literary texts to communicate emotional experience - Justice, Steve (2021)
This thesis, consisting of a novel-length piece of creative writing, entitled Maximum Occupancy, and a critical research report, explores the extent to which an application of the cognitive poetics framework of Text World Theory during the creative writing process has an impact on the reader’s emotional experience of the creative text. It achieves this through an experimental research cycle of practice-led research and research-led practice. Firstly, a piece of creative writing is edited according to the ideas of Text World Theory, then qualitative data is collected through reader responses to two versions of the creative text before the responses are analysed to determine patterns in relation to emotional experience. Finally, the findings of the research are used to inform the rest of the creative writing process. Two data collection sessions were conducted on two separate pieces of writing through open ended questionnaires with the findings applied to the novel-length final outcome of the creative writing.